Ribonucleotides Linked to DNA of Herpes Simplex Virus Type 1 - Hirsch, Ivan (1974)
Cells of a continuous cell line derived from rabbit embryo fibroblasts were infected with herpes simplex type 1 virus (HSV-1) and maintained in the presence of either [5-(3)H]uridine or [methyl-(3)H]thymidine or (32)PO(4)(3−). Nucleocapsids were isolated from the cytoplasmic fraction, partially purified, and treated with DNase and RNase. From the pelleted nucleocapsids, DNA was extracted and purified by centrifugation in sucrose and cesium sulfate gradients. The acid-precipitable radioactivity of [5-(3)H]uridine-labeled DNA was partially susceptible to pancreatic RNase and alkaline treatment; the susceptibility to the enzyme decreased with increasing salt concentration. No drop of activity of DNA labeled with [(3)H]thymidine was observed either after RNase or alkali treatment. Base composition analysis of [5-(3)H]uridine-labeled DNA showed that the radioactivity was recovered as uracil and cytosine. In the cesium sulfate gradient, the purified [5-(3)H]uridine-labeled DNA banded at the same position as the (32)P-labeled DNA. The present data tend to suggest that ribonucleotide sequences are present in HSV DNA, that they are covalently attached to the viral DNA, and that they can form double-stranded structures.